Optimalisasi Pendapatan Asli Daerah Sektor Pariwisata Di Kota Semarang - Bambang Hermanto (Universitas Muhammadiyah Ponorogo, 2021)
The research aims to look at how to optimize the Local Revenue of the tourism sector in Semarang City. The tourism wealth owned by Semarang City should be able to compete with other cities as a tourist destination city. Other advantages are opening up employment opportunities for the community, increasing the tourism industry sector and increasing the Original Revenue of the City of Semarang. This study uses a qualitative method. Data collection techniques used are derived from primary data in the form of observations of phenomena that occur and secondary data in the form of valid documentation. Based on the results of the analysis shows that the tourist attraction in the city of Semarang can be enjoyed by tourists with a variety of destinations, both to enjoy travel (pleasure tourism), recreation (recreation tourism), culture (cultural tourism), sports (sports tourism), trade business affairs (business tourism), and convention activities (convention tourism). Participatory management is an important approach in optimizing the Local Revenue of the tourism sector in Semarang City. Besides, the application of participatory management in optimizing the Local Revenue of the tourism sector in Semarang City aims to empower local communities. Through the implementation of participatory management in optimizing the Local Revenue of the tourism sector in Semarang City, local communities can take advantage of opportunities in many aspects including managers, consumption or restaurant providers, accommodation facilities, transportation and utility souvenirs from household handicrafts. Tourism development planning is carried out by the wishes of the community or sometimes planning is made by residents.